Culture Moderates the Relation Between Perceived Stress, Social Support, and Mental and Physical Health. (August 2016) - Shavitt, Sharon; Cho, Young Ik; Johnson, Timothy P.; Jiang, Duo; Holbrook, Allyson; Stavrakantonaki, Marina
Cultural differences in the relations between perceived stress and mental and physical health, and the role of social support in buffering these relations, are examined in a survey of multiple U.S. cultural/ethnic groups. Findings from a health survey of N = 603 adults comprising approximately equal numbers of non-Hispanic Whites, Mexican Americans, Korean Americans, and African Americans show that perceived stress is negatively correlated with one's perceived mental and physical health, in line with previous research. However, the role of social support in mitigating this relationship is culturally contingent. A buffering effect of social support on the relation between perceived stress and both mental and physical health was only observed for Mexican Americans, not for the other cultural/ethnic groups. These patterns are discussed in the context of research on differences in social help seeking among distinct types of collectivistic cultural groups. The findings are consistent with recent research on horizontal versus vertical collectivism that highlights the importance of sociability and benevolence in Latin American cultural contexts. The results affirm the importance of distinguishing between collectivistic cultures in understanding how social support may impact mental and physical health.